Mechanisms for increasing digital inclusion of the population to ensure information security of the state (Economics and region, 2023)
The article explores the meaningful aspects of the concept of "digital inclusion of the population" and defines it as the ability of the population to use information and communication technologies to improve their everyday life, which is ensured by the availability of these goods and services for the population, as well as the availability of skills for their effective use. An approach to the integral assessment of the digital inclusion of the population based on the combination of the method of principal components, the Fishburn formula and additive convolution has been developed. The dynamics of the level of digital inclusion of the population were analyzed and the main regularities of its volatility were determined. In particular, during 2006-2016, an increase in the level of digital inclusion of the population was recorded in Ukraine, while in 2017-2020, the level of the indicator practically did not vary. Causal relationships between the level of digital inclusion of the population and the information security of the state were established using regression modeling: an increase in the digital inclusion of the population by 1 unit leads to an increase in the level of information security of the state by 92,908 units. The main barriers to increasing the digital inclusion of the population are identified, namely: insufficient level of development of supporting infrastructure, low adaptability of digital goods and services to the needs of people with disabilities, unavailability of information and communication technologies for people with limited financial capabilities, language restrictions. Taking into account the outlined problems, mechanisms for their elimination are proposed, including the creation of special adult education centers where the level of digital literacy can be increased, leasing of a gadget, the development of financial support programs to cover the costs of education for socially vulnerable and underprivileged population groups, the legislative establishment of the need to develop versions of sites adapted to the needs of people with disabilities. The conceptual principles of ensuring the level of digital inclusion of the population in the context of strengthening the information security of the state have been developed.
Keywords: digitalization; information security of states, information and communication technologies; digital inclusion; digital gaps